2019
DOI: 10.1037/pac0000363
|View full text |Cite
|
Sign up to set email alerts
|

The central role of social identity in oppression, discrimination and social-structural violence: Collective identity stressors and traumas, their dynamics and mental health impact.

Abstract: Development-based trauma framework (DBTF) identified collective identity stressors and traumas (CISTs) and other trauma types, such as personal identity traumas (PITs), physical identity or survival trauma (PISTs), preidentity such as attachment traumas, and postidentity or secondary trauma (IST). We utilized pooled data from 9 samples from different minorities, refugees, and other victims of CIST (N ϭ 2471) that used measures of cumulative trauma, posttraumatic stress disorder (PTSD), cumulative trauma disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…In this study, Christian minority participants in Egypt had higher PTSD, anxiety, and depression scores than participants in the Muslim majority. Increased mental health among a Christian minority in Arabic countries is consistent with social identity and minority stress theories (e.g., Kira et al, 2019c ) and a recent study on Egypt’s Christian minority (Kira & Shuwiekh, in press ), suggesting that this additional stress significantly undermines well-being.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, Christian minority participants in Egypt had higher PTSD, anxiety, and depression scores than participants in the Muslim majority. Increased mental health among a Christian minority in Arabic countries is consistent with social identity and minority stress theories (e.g., Kira et al, 2019c ) and a recent study on Egypt’s Christian minority (Kira & Shuwiekh, in press ), suggesting that this additional stress significantly undermines well-being.…”
Section: Discussionsupporting
confidence: 77%
“…Discrimination is continuous traumatic stress that starts early in adolescence and continues with the person, as long as he/she possesses this identity. The status of self and identity is salient and underlies discriminative acts' dynamics (Kira, 2019;Kira et al, 2019d). Existential anxieties about the person and group statuses that may be the core-specific anxiety in various discrimination types were rarely studied , I. Kira 2020aKira, Templin et al, 2012).…”
Section: Identity (Personal and Collective) Trauma Modelmentioning
confidence: 99%
“…Type III traumas have subtypes or variants that fall under the broader umbrella term of type III trauma, varying in III-a) and COVID-19 (type III-e) intersection Kira et al, 2021c;Solomon & Heide, 1999;Terr, 1995). The macro-dynamics of intersection, polyvictimization, accumulation, and proliferation, and the interaction among preidentity, identity, and post-identity stressors and traumas determine their total health, mental health, and cognitive impact from a life-course perspective (e.g., Kira et al, 2012aKira et al, , 2012cKira et al, , 2012dKira et al, , 2014aKira et al, , 2014bKira et al, , 2018aKira et al, , 2019aKira et al, , 2019bKira et al, , 2019dKira et al, , 2020dKira, Barger et al, 2019, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to a previous study focusing on Syrian refugees (Chung, AlQarni, et al., 2018b; Chung et al., 2017); however, this study found an association between trauma centrality and oppression particularly in terms of violation of basic needs such as privacy, confiscation of personal property, no access to medical care, food, and water. Oppression has been argued as a form of trauma aiming to bring changes to different aspects of individual, social, or collective identity (Kira et al., 2018).…”
Section: Discussionmentioning
confidence: 99%